2021
DOI: 10.3390/diagnostics11050779
|View full text |Cite
|
Sign up to set email alerts
|

MYD88L265P Detection in IgM Monoclonal Gammopathies: Methodological Considerations for Routine Implementation

Abstract: In IgM monoclonal gammopathies MYD88L265P is a prognostic and predictive biomarker of therapy response. MYD88L265P detection is mainly performed by allele-specific quantitative PCR (ASqPCR), however recently, droplet digital PCR (ddPCR) has been proved to be suitable for MYD88L265P screening and minimal residual disease monitoring (MRD). This study compared ASqPCR and ddPCR to define the most sensitive method for MYD88L265P detection in bone marrow (BM), peripheral blood (PB) sorted or unsorted CD19+ cells, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…In 2018, our group contributed to set ddPCR for the identification of the MYD88 mutation; this technique detected mutation in 96% of MW and 87% of IgM-MGUS cases (vs 81% and 58% by QT-PCR, respectively); the concordance rate with QT-PCR amounted to 78% on bone marrow and 68% on peripheral blood samples; in the remaining cases, ddPCR confirmed its advantage. The most interesting finding of this work was the possible application of this molecular tool to the circulating tumor DNA (ctDNA) harvested from plasma [ 88 ] or in the cerebral spinal fluid [ 89 ]. In 2019, another group employed ddPCR for detecting MYD88L265P mutation in a cohort of 39 patients; with a sensitivity of 1 × 10 −3 , the authors identified the mutation in 90% of MW cases, in 44% of patients affected by LPL, in 5% of IgM MM, and no in CLL or mantle cell lymphoma (MCL) cases [ 90 ].…”
Section: Ddpcr Applications In Hematologymentioning
confidence: 99%
“…In 2018, our group contributed to set ddPCR for the identification of the MYD88 mutation; this technique detected mutation in 96% of MW and 87% of IgM-MGUS cases (vs 81% and 58% by QT-PCR, respectively); the concordance rate with QT-PCR amounted to 78% on bone marrow and 68% on peripheral blood samples; in the remaining cases, ddPCR confirmed its advantage. The most interesting finding of this work was the possible application of this molecular tool to the circulating tumor DNA (ctDNA) harvested from plasma [ 88 ] or in the cerebral spinal fluid [ 89 ]. In 2019, another group employed ddPCR for detecting MYD88L265P mutation in a cohort of 39 patients; with a sensitivity of 1 × 10 −3 , the authors identified the mutation in 90% of MW cases, in 44% of patients affected by LPL, in 5% of IgM MM, and no in CLL or mantle cell lymphoma (MCL) cases [ 90 ].…”
Section: Ddpcr Applications In Hematologymentioning
confidence: 99%
“…Therefore, the MYD88 L265P /MYD88 WT ratio might also be proposed as a quantitative marker and useful diagnostic tool for MRD analysis. Recently, digital PCR (dPCR) has been described as more sensitive than AS-qPCR across different specimen types (including plasma-cfDNA), for MYD88 L265P screening and MRD analysis, suggesting that the implementation of dPCR assay in routine diagnostic laboratories might avoid the need for CD19+ selection [62,99].…”
Section: Referencementioning
confidence: 99%
“…Cast-PCR plasma 92 88% 51 80% ND [192] Up to now, there is a lack of consensus regarding the optimal specimen and analytical method for mutational detection in WM, in terms of operating procedures, test sensitivity and result interpretation [99,192]. Researchers must be aware that differences in method sensitivity may lead to both a misclassification of disease status and an overestimation of the efficacy of novel treatments.…”
Section: Bagratuni Et Al 2022mentioning
confidence: 99%
See 1 more Smart Citation
“…A sub analysis showed a 50% major response rate with zanubrutinib in 26 MYD88 WT patients 52 . However, it should be noted that different methods were used in the detection of MYD88L265P mutation, including Sanger sequencing.1, allele specific polymerase chain reaction (PCR) 53 and more recently droplet digital PCR and NGS‐based techniques, making comparison across studies and standardized sensitive detection of MYD88 mutations problematic 54‐57 …”
Section: Future Perspectivesmentioning
confidence: 99%